2015
DOI: 10.1074/jbc.m115.679043
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E Is a Ligand for Triggering Receptor Expressed on Myeloid Cells 2 (TREM2)

Abstract: Background: TREM2 is associated with several neurodegenerative diseases. Results: ApoE bound to TREM2 and increased phagocytosis of apoptotic neurons by microglia. Alzheimer disease (AD) risk-associated TREM2-R47H mutant had a reduced binding to apoE. Conclusion: ApoE is a novel ligand for TREM2. Interaction between apoE and TREM2 likely regulates phagocytosis of apoEbound apoptotic neurons. Significance: Interaction between two AD risk-associated proteins modulates microglial function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
447
4
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 450 publications
(481 citation statements)
references
References 55 publications
26
447
4
4
Order By: Relevance
“…genes involved in cholesterol transport and efferocytosis (Apoe), immunoproteasome formation (Psmb9 and Pbmb8), and efferocytosis and the resolution of inflammation (Anxa1) (43)(44)(45). Taken together, these results show that this set of genes may be responsible for maintaining a reparative phenotype of MDMs.…”
Section: Resultsmentioning
confidence: 83%
“…genes involved in cholesterol transport and efferocytosis (Apoe), immunoproteasome formation (Psmb9 and Pbmb8), and efferocytosis and the resolution of inflammation (Anxa1) (43)(44)(45). Taken together, these results show that this set of genes may be responsible for maintaining a reparative phenotype of MDMs.…”
Section: Resultsmentioning
confidence: 83%
“…Several different ligands for TREM2 have been reported previously including apolipoprotein E (Atagi et al, 2015;Bailey et al, 2015), lipids exposed upon axonal injury (Poliani et al, 2015), nucleic acids released from dying cells (Kawabori et al, 2015) and damage-associated molecular signatures found on bacteria (Daws et al, 2003;N'Diaye et al, 2009). Interestingly, the ADassociated TREM2 R47H variant shows impaired binding to apolipoprotein E or injury-associated lipids (Atagi et al, 2015;Bailey et al, 2015;Poliani et al, 2015). Hence, we speculate that the glycosylation status changes we observed herein for the R47H variant (Figures 1-3) could explain the ligand binding differences between wild-type TREM2 and TREM2 R47H (Atagi et al, 2015;Bailey et al, 2015;Poliani et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the ADassociated TREM2 R47H variant has impaired binding to the apolipoprotein E or injury-associated lipids (Atagi et al, 2015;Bailey et al, 2015;Poliani et al, 2015). However, it is still unknown how this impairment occurs, or how this may relate to AD pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…TREM2 could serve as a microglial sensor for lipid mediators that are released from damaged sensory nerve terminals or other cells in the DH. Recently, apolipoprotein E (ApoE) was reported to be a potent ligand for TREM2, and an Alzheimer's diseaseassociated R47H mutation and other artificial mutations introduced at the same location significantly reduce the affinity of TREM2 for ApoE (Atagi et al, 2015;Bailey et al, 2015). Additionally, ApoE protein was shown to be upregulated in injured DRG neurons in a spinal nerve ligation model (Melemedjian et al, 2013).…”
Section: Trem2 Functionmentioning
confidence: 99%